Leadership Style and Talent Management as Determinants of Business Performance in Digital-Based Startups: Evidence from Indonesia - Mutiara S Mizan (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Leadership and talent management are widely recognized as critical factors in organizational performance, yet their combined influence within digital-based startups remains underexplored, particularly in Indonesia. Despite the rapid growth of Indonesia’s startup ecosystem, limited empirical research has examined how different leadership styles influence business performance through talent management mechanisms. Grounded in the Resource-Based View (RBV), this study investigates the direct and indirect effects of transformational, transactional, and laissez-faire leadership on digital-based startup business performance, with talent management serving as a mediating variable. Using a quantitative correlational design, data were collected from 217 employees and co-founders of Indonesian digital startups through an online survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that all three leadership styles positively and significantly influence business performance both directly and indirectly through talent management. Laissez-faire leadership demonstrated the strongest direct effect on business performance, while talent management significantly contributed to organizational performance and mediated the relationship between leadership styles and performance. The structural model explained 49.8% of the variance in startup business performance. These findings support the RBV perspective by demonstrating that leadership capability and talent management function as strategic organizational resources that contribute to competitive advantage and performance. The study extends existing leadership and startup management literature while providing practical insights for founders and managers seeking to strengthen organizational performance in Indonesia’s evolving digital economy.